Cryobiopsy in morphological verification of central lung cancer with necrosis - I. S. Mamenko; I. V. Vasilev; G. S. Belyaev; M. M. Mortada; A. O. Nefedov; T. A. Novitskaya; P. K. Yablonskiy (Сибирский онкологический журнал, 2023)
Background. The diagnostic yield of a standard forceps biopsy for central lung cancer is 74 %. However, the diagnostic value is significantly reduced in the presence of necrosis in the tumor. In Russia, cryobiopsy for central lung cancer diagnosis is currently used only in a few clinical centers.The purpose of this study is to present a series of clinical cases showing the effectiveness of the cryobiopsy method in the morphological verification of central neoplasms with necrosis.Description of clinical cases. The article presents 3 clinical cases of patients with central lung cancer, in which standard forceps biopsy was ineffective due to the presence of severe necrosis in the tumor. The cryobiopsy performed at the second stage made it possible in all cases to obtain a suffcient amount of morphological material for histological and immunohistochemical studies and to reconalize the lumens of the large bronchi.Conclusion. Cryobiopsy is an effective and safe method of morphological verification of central lung cancer, which has an advantage over standard forceps biopsy, especially in the presence of a visible necrotic component in the tumor structure.